Indian Folk Music and ‘Tropical Body Language’: The Case of Mauritian Chutney - Catherine Servan-Schreiber (South Asia Multidisciplinary Academic Journal)
In Mauritius, the meeting between Indian worlds and Creole worlds, through the migration of the indentured labour which followed the abolition of slavery in 1834, gave birth to a style of music called ‘chutney’. As a result of the African influence on an Indian folk genre, chutney music embodies the transformation of a music for listening into a music for dancing. In this article, the innovations brought into the choreographical dimension of the chutney groups will be taken as a key to understanding the adaptation of Indian rural migrants to a new ‘Indian-oceanic’ way of life through the experience of diaspora.